The development of information storage materials - How microscopy can help? - Petford-Long, A; Portier, X; Shang, P; Cerezo, A; Larson, D (2002)
The response of giant magnetoresistance (GMR) devices depends critically on the film microstructure, with parameters such as layer thickness and interfacial abruptness being crucial. This paper presents results obtained using high resolution electron microscopy (HREM), chemical mapping and atom probe microanalysis. Local variations in the magnetic properties are induced by the microstructure and also when the films are patterned to form small elements, These lead to changes in the magnetization reversal mechanism. Some results of the studies of the magnetization reversal carried out using in situ in Lorentz transmission electron microscopy (LTEM) magnetizing experiments are also included.